Transition‐Metal‐Free Olefinic C−H Azidoalkylthiolation via C(sp3)−S Bond Cleavage of Vinylsulfonium Salts. Issue 17 (9th August 2022) - He, Yuan; Huang, Zilong; Ma, Juan; Lin, Jie; Zhou, Yong‐Gui; Yu, Zhengkun
Abstract: A transition‐metal‐free olefinic C−H azidoalkylthiolation protocol was developed through C( sp 3 )−S bond cleavage of vinylsulfonium salts with sodium azide in air under aqueous conditions. An interrupted Pummerer/nucleophilc azidoalkylation cascade was developed for such a process. The practicability of the synthetic protocol was demonstrated by scale‐up preparation of the azidoalkylthiolated tetrasubstituted alkene products and their transformations to diverse triazole and tetrazole derivatives as well as azidoalkylthio‐funtionalized N ‐heterocyclic compounds. The present synthetic methodology features broad substrate scopes and good functional group tolerance under mild conditions. Abstract :